Toward the Knowledge of the Epidemiological Impact of Acute Rheumatic Fever in Italy - Alberio, Antonino Maria Quintilio; Pieroni, Filippo; Di Gangi, Alessandro; Cappelli, Susanna; Bini, Giulia; Abu-Rumeileh, Sarah; Orsini, Alessandro; Bonuccelli, Alice; Peroni, Diego; Assanta, Nadia; Gaggiano, Carla; Simonini, Gabriele; et al. (Frontiers in Pediatrics, 2021)
Background: To estimate the incidence of Acute Rheumatic Fever (ARF) in Tuscany, a region of Central Italy, evaluating the epidemiological impact of the new diagnostic guidelines, and to analyse our outcomes in the context of the Italian overview. Methods: A multicenter and retrospective study was conducted involving children less than 18 years old living in Tuscany and diagnosed in the period between 2010 and 2019. Two groups were established based on the new diagnostic criteria: High-Risk (HR) group patients, n=29 and Low-Risk group patients, n=96. Results: ARF annual incidence ranged from 0.91 to 7.33 out of 100 000 children in the analysed period, with peak of incidence registered in 2019. The application of HR criteria led to an increase of ARF diagnosis of 30%. Among the overall cohort joint involvement was the most represented criteria (68%), followed by carditis (58%). High prevalence of subclinical carditis was observed (59%). Conclusions: Tuscany should be considered an HR geographic area and HR criteria should be used for ARF diagnosis in this region.